LB1.2 Pilot study of immediate antiretrovirals and behavioural intervention for persons with acute hiv infection: opportunity for interrupting transmission. (13th September 2015) - Rutstein, SE; Pettifor, A; Phiri, S; Pasquale, D; Dennis, A; Hosseinipour, M; Kamanga, G; Nsona, D; Hoffman, I; Miller, WC
Abstract : Introduction: Persons with acute HIV infection (AHI) contribute disproportionately to transmission. In a pilot study, we evaluated a short-term, behavioural and biomedical intervention among persons with AHI in Malawi. Methods: We enrolled persons with AHI. AHI was defined as negative or discordant antibody test (s) with detectable virus. Persons were randomised 1:2:2 to standard counselling (SC), a four-session behavioural intervention (BI), or behavioural intervention plus 12 weeks of antiretrovirals (BIA), and followed 26–52 weeks. ARV resistance was assessed at baseline and after therapy. Participants were asked to refer partners for testing. Follow-up was completed in August 2014; phylogenetic analyses were completed in May 2015. Results: We identified 59 persons with AHI and enrolled 46 (9 [SC], 18 [BI], 19 [BIA]). Average age was 25; 61% were male. Median viral load (VL) was 5.9 log copies/ml (6.7 [SC]; 5.1 [BI]; 6.1 [BIA]). At week four, 64% (11/17) of BIA participants were suppressed (<1000 copies/ml), versus 12% (2/17 [BI]) and 25% (2/8 [SC]) (p < 0.001). VL rebounded after ARV discontinuation. No ARV resistance accumulated after exposure. Risk behaviours decreased across all arms: participants reported fewer sexual encounters at week four versus baseline (4.4 vs 8.7, p = 0.003) and fewer encounters without condoms (21% vs 63%, p < 0.001). 41% (19/46) referred partners; 15 were HIV-infected and 2 seroconverted during follow-up. 13 of 15 HIV-infected partners had nucleotide sequences available; 92% (12/13) were phylogenetically linked with AHI index. Conclusion: ARV quickly reduced viremia below transmissible levels and did not induce resistance; however, patients experienced rapid virological rebound after discontinuation. Sexual risk decreased rapidly in all arms. Most referred partners with available sequences were linked transmissions with the AHI index. Early diagnosis with standard AHI counselling and early ARV referral may be sufficient to reduce transmission risk. Disclosure of interest statement: This study was supported by the National Institutes of Health, USA; ARVs donated by Merck and Gilead.